Do initial respondents differ from callback respondents? Lessons from a mobile CATI survey - Vicente, P.; Marques, C. (Social Science Computer Review, 2017)
Mobile phones are increasingly being used to conduct mobile CATI-Computer Assisted Telephone Interview surveys and some say it is just a question of time before they replace fixed phones. Although mobile phones allow their users to be called anywhere and at any time, a 100% response rate is unlikely to be achieved with a single call attempt. Callbacks are costly and delay fieldwork completion but they are worth the effort when better overall response rates as well as those for specific subgroups of the population are obtained. Using data collected on a nationwide mobile CATI survey, this paper investigates the differences between initial and callback respondents. Findings reveal that although the majority of interviews were achieved with a single call attempt, the initial sample differed from the callback sample in terms of the age and residence of respondents. Additionally, callback respondents were more likely to be interviewed outside home.